Henoch–Schönlein Purpura with Gastrointestinal Involvement in an Adult Patient: A Case Report - Seno Lamsir; Endra Yustin Ellistasari; Ervina Rosmarwati; Prasetyadi Mawardi (Rumah Sakit Umum Daerah Dr. Moewardi, 2026)
Introduction Henoch–Schönlein purpura (HSP), also known as IgA vasculitis, is a systemic small-vessel vasculitis characterized by IgA immune complex deposition. Although predominantly a childhood disease with a generally favorable prognosis, adult cases often exhibit more severe systemic involvement, particularly affecting the gastrointestinal tract and kidneys. Case A 22-year-old female presented with palpable purpura on the extremities, arthralgia, and melena. Physical examination revealed confluent purpuric lesions over the arms and legs. Endoscopy revealed esophagitis and antral gastritis. Skin biopsy demonstrated flattening of rete ridges and perivascular infiltrates, consistent with leukocytoclastic vasculitis. The patient was treated with intravenous methylprednisolone and supportive therapy, resulting in significant improvement of skin lesions, joint pain, and resolution of gastrointestinal bleeding. Discussion Adult HSP is less common but typically has a more severe course compared to pediatric cases. Gastrointestinal involvement, as seen in this case, may present as bleeding, ischemia, or ulceration, and can be life-threatening. Corticosteroids are effective in controlling inflammation and alleviating symptoms but do not prevent renal complications. Continuous renal monitoring is crucial, as kidney involvement remains the primary determinant of long-term prognosis. Conclusion This case highlights the clinical relevance of HSP in adults, where gastrointestinal manifestations may predominate and require aggressive management. Long-term follow-up, especially for renal involvement, is essential to improve outcomes.